PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENCIPTAKAN BUDAYA RELIGIUS DI UPT SPF SMPN 18 MAKASSAR - Ramadhani, Fadhila; Nashir, Ahmad; Alamsyah, Alamsyah (LPPM Universitas Islam 45, 2024)
The aims of this study were: to find out the learning interest of children with special needs (slow learning) at the 1st storey Mallengkeri Inpres Elementary School. the role of Islamic religious education teachers in increasing interest in learning children with special needs (Slow Learning) in learning Islamic religious education at the Mallengkeri Pres. Elementary School with Grade 1. The type of research used is a qualitative method. Data collection techniques in this study are observation, interviews, and documentation. The data sources in this study are primary and secondary data sources. Meanwhile, the objects in this study were school principals, Islamic religious education teachers, slow learning students at Grade I Mallengkeri Pres Elementary School. The results showed that slow learning students at Grade I Pres Mallengkeri Grade VI Elementary School had a high interest in learning. can be characterized by the level of craftsmanship and activeness of slow learning students in the learning given by Islamic religious education teachers at school. learning strategies carried out by Islamic religious education teachers in dealing with slow learning children at Grade I Mallengkeri Elementary School Grade VI, namely by implementing various strategies in learning such as using a student-centered learning approach with an individual system and a remedial approach, then the methods used by the teacher in Slow learning students are lecture methods, questions and answers, exercises, demonstrations with picture books about the practice of prayer and ablution, reward punishment and assignment methods.